Dutch Atlantic connections, 1680-1800 : linking empires, bridging borders - Oostindie, Gert; Roitman, J. (Jessica V.) (Atlantic world (Leiden, Netherlands), 2014)
This title is available online in its entirety in Open Access. Dutch Atlantic Connections reevaluates the role of the Dutch in the Atlantic between 1680-1800. It shows how pivotal the Dutch were for the functioning of the Atlantic system by highlighting both economic and cultural contributions to the Atlantic world.